Mortality in patients with carbapenem-resistant Pseudomonas aeruginosa with and without susceptibility to traditional antipseudomonal β-lactams. Issue 4 (17th December 2021) - Howard-Anderson, Jessica; Bower, Chris W; Smith, Gillian; Satola, Sarah W; Jacob, Jesse T
Abstract: Background: Carbapenem-resistant Pseudomonas aeruginosa (CRPA) isolates can frequently retain susceptibility to traditional antipseudomonal β-lactams including cefepime, ceftazidime and piperacillin/tazobactam. Objectives: This observational study aimed to determine the proportion of CRPA isolates that were susceptible to all tested other traditional antipseudomonal β-lactams (S-CRPA) and assess whether patients with S-CRPA had improved 30 day mortality compared with patients with NS-CRPA (non-susceptible to cefepime, ceftazidime or piperacillin/tazobactam). Methods: Patients with CRPA isolated from normally sterile sites, urine, lower respiratory tracts and wounds were identified using active population- and laboratory-based surveillance through the Georgia Emerging Infections Program from August 2016 to July 2018 in Atlanta, GA, USA. Only unique patients who were hospitalized at the time of, or within 1 week of, culture were included. We excluded patients with cystic fibrosis. Multivariable logistic regression estimated the association between S-CRPA and 30 day mortality. Results: Among 635 adults hospitalized with CRPA, 219 (34%) had S-CRPA. Patients with S-CRPA were more likely to be white (50% versus 38%, P = 0.01) and live in a private residence prior to culture (44% versus 28%, P < 0.01), and less likely to have required ICU care within the prior week (23% versus 36%, P < 0.01) compared with patients with NS-CRPA. Compared with those with NS-CRPA, patients with S-CRPA had an increased 30 day mortality (18% versus 15%, adjusted OR 1.9; 95% CI 1.2–3.1). Conclusions: S-CRPA was associated with higher 30 day mortality than NS-CRPA in hospitalized patients. The reason for this observed increase in mortality deserves further investigation.